1986
DOI: 10.1152/jappl.1986.60.2.353
|View full text |Cite
|
Sign up to set email alerts
|

The alveolar macrophage

Abstract: The alveolar macrophage is one of the few tissue macrophage populations readily accessible to study both in the human and in animals. Since harvesting of these cells by bronchoalveolar lavage was first described in 1961, alveolar macrophages have been extensively investigated. This population is the predominant cell type within the alveolus, and undoubtedly serves as the first line of host defense against inhaled organisms and soluble and particulate molecules. Early studies focussed on this endocytic role and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
189
2
3

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 445 publications
(200 citation statements)
references
References 0 publications
4
189
2
3
Order By: Relevance
“…Macrophages are known to play a variety of important roles in the lung, including that of serving as accessory cells. While alveolar macrophages are the best-characterized accessory cells (Fels and Cohn, 1986), in our study PIMs showed a more vigorous response to halothane than any other pulmonary macrophage .…”
contrasting
confidence: 42%
“…Macrophages are known to play a variety of important roles in the lung, including that of serving as accessory cells. While alveolar macrophages are the best-characterized accessory cells (Fels and Cohn, 1986), in our study PIMs showed a more vigorous response to halothane than any other pulmonary macrophage .…”
contrasting
confidence: 42%
“…As the resident professional phagocyte, AMs provide a first line of host defense by internalizing and degrading microbial pathogens encountered on the respiratory surface. 1 Upon pathogen exposure, AMs express cytokines that influence recruitment and activation of inflammatory cells and modify adaptive immune responses in a pathogen-selective fashion. 2 In this way, cytokines released from pathogen-exposed AMs provide important molecular "links" between innate and adaptive immunity in the lung.…”
Section: Introductionmentioning
confidence: 99%
“…CAM are far more effective than AAM in killing intracellular pathogens although they do not take in bacteria as profusely as AAM. Alveolar macrophages, which are the resident macrophage population in the lung, have been classified as alternatively activated due to the receptor types they express and their balanced, regulated immune response (9). Hence, AAM are the dominant macrophage type in healthy lung tissue.…”
mentioning
confidence: 99%